Celebration capitalism, sports mega-events, and the Tokyo 2020 Olympics - Boykoff, J. (Journal of Sport and Gender Studies, 2021)
The Olympic Games are an enormous event that blends sports, media, and commercialism. The Games are a festival of top-tier athletics swaddled in corporate cash and bolstered by high viewership numbers. Billions of people in over 200 countries around the globe watch the Olympics on television, creating a massive marketing platform for the International Olympic Committee, the group that oversees the Games. There is no question that capitalism is firmly bricked into the Olympics. This presentation involves three central sections. First, I outline the theory of "celebration capitalism", explain its principle elements, and demonstrate how it relates to Naomi Klein's framework of "disaster capitalism." I argue that celebration capitalism is helps organize our thoughts on the modern Olympics and best captures the political and economic dynamics at the core of the Games in the 21st century. Second, I draw from research on particular Olympic Games to demonstrate how celebration capitalism manifests in specific policies, practices, and problems in the host city. Third, I examine how celebration capitalism has taken shape in Tokyo as the city prepares to host the postponed "2020" Summer Olympics. "Tokyo 2020" illuminates celebration capitalism in many ways, from the overspending of public money to greenwashing to the militarization of the public sphere. I conclude by explaining how the tenets at the core of celebration capitalism - and the problems they create in the host city -increasingly stimulate anti-Olympics activism, and how a stable, transnational anti-Games network has emerged linking protesters from around the globe.